Ethnophysics in physics education : a systematic review of trends, methods, and learning applications - Iffah Khairiyah Ismayanti; Efa Musrifah; Heru Kuswanto (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2026)
Physics is often considered abstract and distant from everyday life, thus decreasing student learning interest. Ethnophysics has emerged as a pedagogical approach that connects scientific principles with local wisdom. This study, a Systematic Literature Review (SLR), examined 57 articles (2016–March 2026) using the PRISMA protocol and bibliometric mapping with VOSviewer. Results show an increase in publications since 2022, influenced by the Independent Curriculum policy in Indonesia. The dominant topics are Classical Mechanics and Thermodynamics, many of which have been developed through Research and Development (R&D) into digital media such as e-modules, flipbooks, and AR/VR. Empirical evidence confirms that ethnophysics improves students' scientific literacy, critical thinking, and cultural identity. However, research is still limited to the integration of local wisdom with modern physics and electromagnetism. Future studies should emphasize longitudinal research to assess long-term impacts and expand the scope of culture-based physics curricula